2017
DOI: 10.1186/s13014-017-0915-8
|View full text |Cite
|
Sign up to set email alerts
|

Conventional fractionation should not be the standard of care for T2 glottic cancer

Abstract: BackgroundThe aim of this study was to report outcomes and late toxicity following hypofractionated accelerated radiotherapy for T2 glottic cancers. We highlight the importance of hypofractionated treatments with shorter overall treatment times, in improving outcomes for T2 glottic cancers. We also compare the biologically effective dose of hypofractionated regimes, with conventional fractionation.MethodsOne hundred twelve patients with T2 glottic cancer were treated between January 1999 and December 2005. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Recent research has shown that there is a trend towards hypofractionated radiotherapy (e.g. in prostate carcinomas [25][26][27][28] and in some H & N tumours 29,30 ). The phase III prostate advances in comparative evidence (PACE) trial even investigates extreme hypofractionation in prostate cases, using doses of > 7 Gy per fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that there is a trend towards hypofractionated radiotherapy (e.g. in prostate carcinomas [25][26][27][28] and in some H & N tumours 29,30 ). The phase III prostate advances in comparative evidence (PACE) trial even investigates extreme hypofractionation in prostate cases, using doses of > 7 Gy per fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on large series from cancer registries (42, 43), prospective clinical databases (44), meta-analyses (41), and prospective randomized trials (4547) demonstrated favorable results with altered fractionation either by means of hypofractionation and/or acceleration. The possible effect of hypofractionation is probably based on its treatment-accelerating effect, rather than the exploitation of the β value (44, 45, 48, 49). As reported so far, long-term toxicity is not a major point of concern with accelerated or moderately-hypofractionated irradiation (46, 47, 50), which is in line with the biological rationale regarding the time factor (49).…”
Section: Resultsmentioning
confidence: 99%
“…The possible effect of hypofractionation is probably based on its treatment-accelerating effect, rather than the exploitation of the β value (44, 45, 48, 49). As reported so far, long-term toxicity is not a major point of concern with accelerated or moderately-hypofractionated irradiation (46, 47, 50), which is in line with the biological rationale regarding the time factor (49). It can be safely applied and may be preferred due to its benefits in terms of costs, logistics, and patient comfort.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have evaluated hypofractionated RT for early glottic cancer with fraction sizes up to 2.5 Gy, and resulted in better local control or survival rates [4,6,15]. Furthermore, there was an effort to apply 52.5 Gy in 3.28 Gy per fraction to early glottic cancer, with a 5-year LC rate of 3.5 Gy per fraction for glottic cancer 93% and 82% for T1 and T2 tumors, respectively, which is comparable to other fractionation regimens [8,16]. It should be noted that the fractionation scheme of the current study has relatively high biologically effective dose (BED).…”
Section: Discussionmentioning
confidence: 99%